Evaluation of the anti-caries effect of a glass ionomer sealant and a fluoride varnish - Scotti, Cassiana Koch (2016)
Objective: The aim of this in vitro study was to evaluate the mineral loss of enamel treated with a glass ionomer-based sealant and a fluoride varnish after pHcycling, through the analysis of the microhardness of the enamel as well as the evaluation of Ca/P/F ratio by Energy-dispersive X-ray spectroscopy analysis (EDS). Methods: Thirty six bovine enamel blocks were analyzed for microhardness and randomly assigned to one of the following three treatment groups (n = 12): G1 Clinpro XT Varnish (3M-ESPE); G2 Duraphat (Colgate - Palmolive); or G3 No treatment. The specimens were subjected to pH-cycling for 7 days. Subsequently, they were analyzed by EDS, and the final evaluations of the microhardness at standard distances from the treatment material as well as the cross-sectional microhardness at standard distances from the outer surface of the enamel were performed. Results: The EDS findings revealed that, in G3, the loss of calcium and phosphorus was significantly higher than G1 and G2 after pH-cycling; however, there were no significant differences in the initial and final fluoride ion concentrations among the three groups. The values of the surface microhardness and crosssectional microhardness in G1 and G2 were higher than those in G3, at different distances of the materials. Conclusion: Within the limitations of this study, it may be concluded that both the evaluated materials were able to partially inhibit enamel demineralization when subjected to a dynamic pH-cycling model.